Discrete lotsizing and scheduling by batch sequencing - Carsten Jordan; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1997)
The discrete lotsizing and scheduling problem for one machine with sequence dependent setup times and setup costs is solved as a single machine scheduling problem, which we term the batch sequencing problem. The relationship between the lotsizing problem and the batch sequencing problem is analyzed. The batch sequencing problem is solved with a brauch & bound algorithm which is accelerated by bounding and dominance rules. The algorithm is compared with recently published procedures for solving variants of the DLSP and is found to be more efficient if the number of items is not large.
Keywords: 650; DISCRETE LOTSIZING AND SCHEDULING; SEQUENCE DEPENDENT SETUP TIMES AND SETUP COSTS; BATCH SEQUENCING; BRANCH & BOUND ALGORITHM; BOUNDING/DOMINANCE RULES